ANTHROPOGENIC ACTIVITIES OF ILLEGAL MINE RESISTANCE TO THE ENVIRONMENT AND SOCIAL ECONOMIC DYNAMICS - A. Silvan Erusani; Ardian Chandra Aji (International Journal of Social Science, 2022)
This study aims to assess the anthropogenic activities of illegal mining on the environment and socio-economic dynamics at the location of gold mining without a permit in Madong Raya Village, Tanah Pinoh District, Melawi Regency. The research approach is qualitative with the aim of producing a descriptive analysis related to the data collected based on the construction of existing theories and literature. Field findings reveal that anthropogenic activities are still carried out by local communities in the defense of illegal mining and have an impact on environmental degradation and meet daily needs in financing families and the strength of interaction between residents in utilizing natural resources. Research data analysis was carried out in a descriptive way, namely the impact of illegal mining and social impacts society from anthropogenic activities causing prolonged degradation. Anthropogenic activities cause the decline in environmental quality and local people's livelihoods in meeting daily needs as well as developing community capacity and empowerment in a participatory, equitable, and environmentally friendly manner so as to create social and economic resilience as well as resilience to the effects of external changes by not carrying out mining activities. gold is illegal considering that there are casualties due to the mining